2020
DOI: 10.1111/jcmm.14945
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain and extraterminal domain inhibitor enhances the antitumor effect of imatinib in gastrointestinal stromal tumours

Abstract: In gastrointestinal stromal tumours (GISTs), the function of bromodomain‐containing 4 (BRD4) remains underexplored. BRD4 mRNA abundance was quantified in GISTs. In the current study, we investigated the role of BRD4 in GISTs. Our results show a significant enhancement in BRD4 mRNA and a shift from very low‐risk/low‐risk to high‐risk levels as per NCCN specifications. Overexpression of BRD4 correlated with unfavourable genotype, nongastric location, enhanced risk and decreased disease‐free survival, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…In our study, we observed that BET inhibition exhibited two independent downstream effects in CRC cells, including MYC repression and AKT inhibition. AKT inhibition by BETi is consistent with previous reports, showing that BETi repressed RTK expression and subsequently inactivated PI3K/AKT pathway 36,37 . Since RTKs serve as an upstream activator of PI3K/AKT, inhibition of AKT phosphorylation by BETi is likely to be attributed to the blockade of RTK expression, such as EGFR family and KIT.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we observed that BET inhibition exhibited two independent downstream effects in CRC cells, including MYC repression and AKT inhibition. AKT inhibition by BETi is consistent with previous reports, showing that BETi repressed RTK expression and subsequently inactivated PI3K/AKT pathway 36,37 . Since RTKs serve as an upstream activator of PI3K/AKT, inhibition of AKT phosphorylation by BETi is likely to be attributed to the blockade of RTK expression, such as EGFR family and KIT.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we observed that BET inhibition exhibited two independent downstream effects in CRC cells, including MYC repression and AKT inhibition. AKT inhibition by BETi is consistent with previous reports, showing that BETi repressed RTK expression and subsequently inactivated PI3K/AKT pathway 35 , 36 . Since RTKs serve as an upstream activator of PI3K/AKT, inhibition of AKT phosphorylation by BETi is likely to be attributed to the blockade of RTK expression, such as EGFR family and KIT.…”
Section: Discussionsupporting
confidence: 93%
“…Several core transcription factors have been revealed to play essential roles in driving GIST cell proliferation and metastasis by binding to enhancers of GISTassociated genes and facilitating KIT gene expression [13][14][15]. Moreover, a previous study revealed that the KIT-regulated enhancer domain in GISTs could be targeted by BRD4, a key activator of RNAPII transcription at active chromatin marks, and the BET bromodomain inhibitor (BBI) can downregulate KIT transcription [34,35]. Therefore, characterization of transcription factor deregulation in GIST may provide innovative insights into the pathogenesis mechanisms and offer new therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%